1981
DOI: 10.1128/jb.147.2.297-304.1981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the tetracycline resistance promoter and repressor in transposon Tn10

Abstract: The structural and regulatory functions encoding tetracycline resistance in transposon Tn10 lie within a 2,700-base pair region. Using recombinant plasmids with different deoxyribonucleic acid sequences adjacent to a HincII site in this region, we located the promoter controlling the expression of tetracycline resistance. These various sequences conferred altered levels of tetracycline resistance. Plasmids containing deletions of a 695-base pair HincII fragment were constitutive and showed the loss of a 23,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 43 publications
6
75
1
Order By: Relevance
“…Regulatory mutants of TnlO that express tetracycline resistance constitutively have been isolated (10)(11)(12). Most of the data available are consistent with a model of negative control (6,40,41), although the observation that regulatory mutants of TnlO often have a dominant constitutive phenotype may indicate that a more complex type of control exists (11). To investigate the regulation of the tetracycline resistance of TnlO in detail, we isolated mutants defective in the regulation of resistance.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Regulatory mutants of TnlO that express tetracycline resistance constitutively have been isolated (10)(11)(12). Most of the data available are consistent with a model of negative control (6,40,41), although the observation that regulatory mutants of TnlO often have a dominant constitutive phenotype may indicate that a more complex type of control exists (11). To investigate the regulation of the tetracycline resistance of TnlO in detail, we isolated mutants defective in the regulation of resistance.…”
mentioning
confidence: 97%
“…Evidence for the existence of a regulatory gene for tetracycline resistance was provided by mutant analyses, gene fusions, and regulatory studies. From the phenotypes of deletion mu-tants generated by restriction enzymes, it was concluded that the regulatory region is located on the left side of the tetA gene (10,40), as shown in Fig. 1.…”
mentioning
confidence: 99%
“…This is particularly true for regulatory proteins which negatively control their own synthesis like the cIgene product from the Escherichia coli phage X (Johnson et al, 1980). Negative control of its own expression has also been reported for the Tn 10-encoded TET repressor which regulates the expression of the tetracycline resistance operon on TnIO (Beck et al, 1982;Wray et al, 1981;Hillen et al, 1982). The control of transcription in this operon is of particular interest because it is complex with overlapping divergent promoters (Bertrand et al, 1983;Hillen et al, 1984) and a tandem arrangement of nearly identical operator sequences separated by 12 bp .…”
Section: Introductionmentioning
confidence: 91%
“…Due to its negative control, early attempts to prepare the repressor protein were only partially successful (Yang et 1976). Even the construction of a constitutive overproducer of the TET repressor employing a weak promoter from Tn5 (Wray et al, 1981) did not result in purification of the TET repressor to homogeneity (Hillen et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation